Impact of Social Media on the Development of New Products, Marketing and Customer Relationship Management in Kosovo - Rrezarta Gashi; Hana Gashi Ahmeti (Ital Publication, 2021)
The main objective of this paper is to highlight the importance of social media in the development of enterprises, and in particular the development of new products, and highlight the role of social media in customer relations, where the development of a new product is one of the most important elements for an enterprise. For the realization of this paper, a special questionnaire was used, where its structure was divided into three parts, where in the first part are presented the demographic questions, in the second part are the questions related to the use of social media, as and the third part includes questions related to the productivity of products and the enterprise in general. Participants in this paper were 350 companies. The paper results are presented through descriptive analysis, correlation analysis, and regression. Based on the results of this paper, we can say that Kosovar companies through social media establish relationships with their customers and keep them informed, which also greatly influences the development of new products, as well as organizational performance. Also what is noticed in this paper is the enterprises have managed to improve the quality of products through the study of customer feedback. The results also show that the use of social media to create relationships with customers and inform them, statistically affect the organizational performance and product success of Kosovo enterprises. The results also show that social media have an impact on organizational performance, the success of the company, close customer relationships, and timely information. Doi: 10.28991/esj-2021-01263 Full Text: PDF